Numerical Solutions on Flow and Heat Transfer of Non-Newtonian Jeffrey Micropolar Fluid - Al-Sharifi, H. A. M.; Abdul Rahman, Mohd Kasim; Mohd Zuki, Salleh; Shafie, S. (Informatics Publishing Limited, 2017)
Objectives: The present study investigates the problem of flow and heat transfer on non-Newtonian Jeffrey micropolar fluid numerically. The flow that moving across a stretching sheet has been considered embedded with constant wall temperature. Methods/Statistical Analysis: The suitable similarity transformations are used to transform the governing boundary layer equation into ordinary differential equations. This is very important in order to reduce the complexity of the equation. The numerical results are obtained using Keller box method. Findings: The procedure to validate the present results has been run and the outcomes obtained are outstanding. The results obtained in graphical form show the parameter Deborah number boost the value of fluid velocity. At near the surface, the larger values of Deborah number led to decrease the distribution of micro rotation of fluid but after η > 1.6 the trend has changed oppositely. Application/Improvements: The results from this research give advance understanding on the micro rotational effects toward the non-Newtonian fluid flow.